An Android Application for Animated Lecture Retrieval in E-Learning - Osikoya Damilola; Adeleke Oluwalani (European Alliance for Innovation (EAI), 2013)
The use of mobile devices in content delivery has made instructional learning more compact and convenient for learners and tutors. This is due to recent development in mobile technology and its use in supporting educational and instructional activities. The efficacy of creating instructional contents still serves as a major confrontation for educators at all institutions in all spheres of education. The main objective of this project is to integrate the use of mobile technology with instructional content retrieval to improve teaching and learning. In this paper, we have developed a mobile application for content retrieval in mobile learning. This application is linked to a repository where instructional contents reside. This approach would help students access instructional contents anywhere away from their regular learning environment using their mobile device. Students would also have access to an E-learning website whose database would also serve as a repository to the mobile application. The effectiveness of this work is to provide an ease of learning for students by offering a tool that would help access course materials from anywhere. Students in the scientific domain would also have the opportunity to understand abstract concepts on their own by having access scientific animated contents on their mobile devices as well as on the E-learning website.